The Functional Properties of Buffalo skin Gelatin Extracted Using Crude Acid Protease from Cow’s Abomasum - Sri Mulyani; Umar Santoso; Yudi Pranoto; Francis M.C. Setyabudi; Anang Mohamad Legowo (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2019)
The study was investigated the functional properties of buffalo skin gelatine. Gelatine was extracted from swamp buffalo skin using crude acid protease from cow’s abomasum (CAPC) in concentration variation 0; 2.5; 5; and 7.5 U/mg. The temperature to hydrolysis included at 28 °C, 37°C and 40°C. The emulsion activity index (EAI), Emulsion stability index (ESI), foaming expansion (FE) and foaming stability (FS) were investigated. The interaction between CAPC concentration and hydrolysis temperature has a significant effect (P <0.05) on the emulsion activity index (EAI), emulsion stability index (ESI), foaming expansion (FE) and foaming stability (FS). The highest EAI was obtained in CAPC concentration of 5 U /mg, hydrolysis temperature of 40°C, which was 12.04 m2/g. The higher concentration of CAPC decreased the ESI. The hydrolysis temperature of 40°C produces higher FE than 28°C and 40°C. The highest FE is obtained at CAPC 5U/mg, 37°C hydrolysis temperature, which is 102.93%. The FS values range from 44.91-55.00%. This value is higher than commercial gelatin (bovine skin gelatin) which is 34.90%. The conclusion of this study is that buffalo skin gelatin with the best functional properties was obtained using CAPC 5 U/mg, the hydrolysis temperature of 40°C.